2016
DOI: 10.1007/s00109-016-1452-x
|View full text |Cite
|
Sign up to set email alerts
|

C-myc overexpression drives melanoma metastasis by promoting vasculogenic mimicry via c-myc/snail/Bax signaling

Abstract: High c-Myc expression is associated with tumor metastasis and poor prognosis in human melanoma. c-Myc upregulates Snail expression to promote EMT via the TGF-β/Snail/Ecadherin signal pathway. c-Myc leads to cell death by upregulating Bax expression causing a lower Bcl2/Bax ratio under severe hypoxic conditions. c-Myc promotes vasculogenic mimicry and linearly patterned programmed cell necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 40 publications
3
53
0
1
Order By: Relevance
“…A few studies have demonstrated that c-Myc overexpression promotes EMT and facilitates vasculogenic mimicry (VM), 37 wherein vessel-like structures form via aggressive tumor cells. VM has been linked with prolonged tumor angiogenesis, higher metastatic risk and poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have demonstrated that c-Myc overexpression promotes EMT and facilitates vasculogenic mimicry (VM), 37 wherein vessel-like structures form via aggressive tumor cells. VM has been linked with prolonged tumor angiogenesis, higher metastatic risk and poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in the latter prompted us to examine a possible role of c‐Myc as Myc was shown to directly upregulate NOXA in melanoma and pancreatic cancers and also directly regulate BIM . Myc expression is frequently dysregulated and elevated in cancer cells, including melanoma . Myc affects biological functions such as cell division, growth and metabolism and can promote apoptosis if expressed highly .…”
Section: Discussionmentioning
confidence: 99%
“…62,63 Myc expression is frequently dysregulated and elevated in cancer cells, including melanoma. 64,65 Myc affects biological functions such as cell division, growth and metabolism and can promote apoptosis if expressed highly. 63,66 In our study, both BRAFi and HDACi decreased expression of Myc, in agreement with studies on MEK inhibitors in triple negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the MYC oncogene is known to lead to cellular transformation and dysregulated programmed cell death (Blum, Hao, & McCarthy, 2015;Evan & Littlewood, 1998;Hoffman & Liebermann, 2008;Lin et al, 2017;Meyer & Penn, 2008). Lin et al, (2017) have reported that c-Myc overexpression can increase invasiveness and metastasis of melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the MYC oncogene is known to lead to cellular transformation and dysregulated programmed cell death (Blum, Hao, & McCarthy, 2015;Evan & Littlewood, 1998;Hoffman & Liebermann, 2008;Lin et al, 2017;Meyer & Penn, 2008). Lin et al, (2017) have reported that c-Myc overexpression can increase invasiveness and metastasis of melanomas. Several reports have also shown that amplification of the MYC oncogene is associated with advanced and metastatic melanomas and that it might also be a marker for predicting poor prognosis (Bastian et al, 2002;Grover et al, 1999;Grover, Ross, Wilson, & Sanders, 1997).…”
Section: Discussionmentioning
confidence: 99%